1989
DOI: 10.1016/0006-8993(89)91018-4
|View full text |Cite
|
Sign up to set email alerts
|

Corticostriatal cells in comparison with pyramidal tract neurons: contrasting properties in the behaving monkey

Abstract: Antidromically identified neurons projecting to the putamen (CPNs) and pyramidal tract neurons (PTNs) were recorded from motor and premotor cortex of a monkey which performed a load-bearing task with the wrist. CPNs appeared as a uniform population with very slowly conducting axons and low spontaneous activity. In contrast to PTNs, they exhibited weak, mostly insignificant correlation with graded steady-state forces, responded to torque perturbations with remarkably long latency, and seemed to discharge much l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
58
3
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 14 publications
16
58
3
1
Order By: Relevance
“…A second subtype of CCS cell identified in rats projects to the brainstem (Donoghue and Kitai, 1981;Cowan and Wilson, 1994;Lévesque et al, 1996a). Although it remains to be investigated how often collaterals are issued from axons descending to the brainstem in the primate (Bauswein et al, 1989), in the rat frontal cortex, brainstem-projecting layer V neurons also frequently innervate the ipsilateral striatum (Lévesque et al, 1996a;Lévesque and Parent, 1998). In this study, we confirmed that CCS and CPn cells are mutually exclusive groups using doublefluorescence markers.…”
Section: Corticostriatal Cell Heterogeneity and Their Intracortical Csupporting
confidence: 76%
“…A second subtype of CCS cell identified in rats projects to the brainstem (Donoghue and Kitai, 1981;Cowan and Wilson, 1994;Lévesque et al, 1996a). Although it remains to be investigated how often collaterals are issued from axons descending to the brainstem in the primate (Bauswein et al, 1989), in the rat frontal cortex, brainstem-projecting layer V neurons also frequently innervate the ipsilateral striatum (Lévesque et al, 1996a;Lévesque and Parent, 1998). In this study, we confirmed that CCS and CPn cells are mutually exclusive groups using doublefluorescence markers.…”
Section: Corticostriatal Cell Heterogeneity and Their Intracortical Csupporting
confidence: 76%
“…The calibration process consisted of varying the I spon currents in each of STN, GP, and SNr while applying background cortical input consisting of low-frequency, unpatterned (Poisson series) spikes with a mean firing rate of f ϭ 3 spikes/s (Bauswein et al, 1989). Such a low rate is insufficient to cause reliable firing in striatum, consistent with numerous striatal recordings (Mahon et al, 2001(Mahon et al, , 2003.…”
Section: Tonic Firing Can Be Fitted From In Vivo Recordings Of Alert mentioning
confidence: 99%
“…Combined single-cell/behavioral studies in primates have found highly specific changes in neuronal activity in relation to (trained) limb movements throughout the nodes of the motor circuit, particularly in relation to movement amplitude/velocity, However, the observed changes in discharge lag behind activity changes in the MC [42][43][44][45], and the activation of (antidromically identified) corticoputaminal neurons lags that of nearby corticofugal projections to brainstem and spinal cord [46,47]. Moreover, lesions interrupting the output of the motor circuit in the sensorimotor territory of GPi in normal primates and individuals with PD or dystonia [48], following pallidotomy, have little or no effect on reaction times, although a slowing of movement is a consistent finding [49][50][51][52].…”
Section: Functional/anatomic Considerations Of the Basal Ganglia Circmentioning
confidence: 99%